Assignment of high-lying bending mode levels in the threshold photoelectron spectrum of NH2: a comparison between pyrolysis and fluorine-atom abstraction radical sources. Issue 29 (7th August 2015) - Holzmeier, F.; Lang, M.; Fischer, I.; Hemberger, P.; Garcia, G. A.; Tang, X.; Loison, J.-C.
<x xml:space="preserve">Abstract</x> The bending mode progression in the photoelectron spectrum of NH2 was observed and assigned up to υ2+ ≤ 5 and Ka+ ≤ 3.